COMPARISON BETWEEN COMPUTED TOMOGRAPHY AND 99m TC‐ PERTECHNETATE SCINTIGRAPHY CHARACTERISTICS OF THE THYROID GLAND IN CATS WITH HYPERTHYROIDISM. Issue 6 (23rd August 2013) - Lautenschlaeger, Ines E.; Hartmann, Antje; Sicken, Julia; Mohrs, Sabrina; Scholz, Volkher B.; Neiger, Reto; Kramer, Martin
Abstract : Scintigraphy is currently the reference standard for diagnosing feline hyperthyroidism; however, computed tomography (CT) is more widely available in veterinary practice. The purposes of this prospective study were to describe the CT appearance of thyroid glands in cats with hyperthyroidism and compare CT findings with findings from 99m Tc–pertechnetate scintigraphy. Twenty‐five adult hyperthyroid cats were included. Plain CT images were acquired for each cat and the following characteristics recorded for each thyroid lobe: visibility, delineation, position, attenuation, shape, and subjective size. Scintigraphic images were also acquired and the following characteristics recorded: radiopharmaceutical uptake, delineation, ectopic foci, shape, and subjective size. In CT images, thyroid lobes were most commonly found between the second and fourth cervical vertebrae, dorsolateral to the trachea. Affected thyroid lobes (based on scintigraphy reference standard) were most commonly oval and moderately enlarged in CT images. A heterogeneous attenuation pattern (isoattenuating to adjacent soft tissues with hypo‐ and hyperattenuating foci) was most commonly found in affected thyroid lobes. A positive correlation ( P < 0.01) was identified between CT and scintigraphy for left‐to‐right thyroid lobe size relationship and subjective size of the larger thyroid lobe. The CT estimated mass was significantly higher (median = 148.8; range = [0;357.6]) for the more active thyroid lobe compared to the less active thyroid lobe (median = 84.6; range = [0;312.3]); (W = 154; P < 0.01). Findings indicated that CT may not reliably differentiate unilateral vs. bilateral hyperthyroidism in cats; however, CT may be a reliable alternative test for correctly identifying the more active thyroid lobe.